Manipulating Pesticide Use to Increase the Production of Wild Game Birds in Britain - Nicolas W. Sotherton; Peter A. Robertson; Simon D. Dowell (National Quail Symposium Proceedings, 2017)
We describe a management technique whereby the adverse effects of pesticides on game-bird chick production were alleviated following selective use or selective avoidance of pesticides on the edges of cereal crops. This technique (known as Conservation Headlands) provided increased amounts of food resources necessary for young gray partridge (Perdix perdix) and ring-necked pheasant (Phasianus colchicus) chicks. The use of Conservation Headlands has consistently increased average numbers of chicks per brood of both species via increases in the densities of arthropods and weed plants. These findings are discussed in the context of the other prerequisites of wild game-bird production in the UK and how these may be altered by recent Government policies to reduce cereal surpluses.
Keywords: Britain; chick foods; Conservation Headlands; gray partridge; indirect effects; pesticides; ring-necked pheasant